Marginalized Memories Architectural Interventions and Reparative Actions in the tenth edition of the Central American Biennale "Todas las vidas" - Villena, Sofia (Universidad de Costa Rica, 2017)
A comparative, critical aproximation to the artistic productions of Óscar Figueroa Chaves, “Intervenciónen el edificio de la UFCO”, and Marcos Agudelo, “Cianómetro”, is presented. These pieces werea part of the tenth Central American Biennale “Todas las vidas”, curated by Tamara Díaz Bringas in theyear 2016, in the provinces of Limón and San José, Costa Rica. The analysis of these works addressesthe complexities found in the ways architectural patrimony in Costa Rica assigns historical meaningand value to public spaces. Through a re-contextualization of the concepts and aesthetic qualities associated to, in the case of Figueroa, the pesticide blue plastic used in banana plantations, and in the caseof Agudelo, the sky, this essay explores the urgent need to make visible, palpable, the way public spacesexclude certain populations from their historical memory in addition to reflecting on what can constitutea reparative actions.